2012
DOI: 10.1007/s10948-012-1449-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Fractal Descriptors Applied to Nanoscale Images

Abstract: -This work proposes the application of fractal descriptors to the analysis of nanoscale materials under different experimental conditions. We obtain descriptors for images from the sample applying a multiscale transform to the calculation of fractal dimension of a surface map of such image. Particularly, we have used the Bouligand-Minkowski fractal dimension. We applied these descriptors to discriminate between two titanium oxide films prepared under different experimental conditions. Results demonstrate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In order to make quantitative estimation of complexity of the obtained structures, the fractional metric Hausdorff-Besicovitch dimension (Feder 1988) was used. It was supposed that the formed structures displayed properties of affine self-similarity in a certain range of scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make quantitative estimation of complexity of the obtained structures, the fractional metric Hausdorff-Besicovitch dimension (Feder 1988) was used. It was supposed that the formed structures displayed properties of affine self-similarity in a certain range of scale.…”
Section: Resultsmentioning
confidence: 99%
“…Such behavior is typical for all fractals. It is well known that the analysis of affine self-similar statistical fractals is used for the study and classification of various surfaces containing random inhomogeneities (Florindo 2012;Krasteva 2013;Raoufi 2001;Yadav 2012). The fractional metric dimension of Hausdorff-Besicovitch was obtained with the use of Fractal Analysis System for Windows Ver.3.4.7 software (Sasaki 1994) from SEM images edited by means of the procedure described below.…”
Section: Resultsmentioning
confidence: 99%
“…Other approaches of extracting particle features from images involve additional mathematical transformations, with examples being wavelet (Kockentiedt & Toennies, ) and Fourier descriptors (Rice et al ., ; Fernandez Martinez et al ., ) or the Minkowski functionals and valuations, where particles are interpreted as graphs, with faces, edges, and vertices (Zhang et al ., ). The application of fractal dimensions (Florindo et al ., , ; Florindo & Bruno, ) is another type of approach to analysing particles. It is also possible to calculate lacunarity (Allain & Cloitre, ) – size distribution of the holes in the fractal.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, these descriptors are capable of providing very rich information about the morphology of the material and, consequently, are a strong method for nanostructured material characterization task. The use of the Volumetric Fractal Descriptors applied to nano structured surfaces was initially proposed in [9]. In that seminal project, was suggested that Fractal Volumetric Descriptors could be used to characterize and analyze such nanostructures, showing the discrimination power on two distinct conditions.…”
Section: Introductionmentioning
confidence: 99%